From motivation, decision-making to action: An fMRI study on suicidal behavior in patients with major depressive disorder. (July 2021) - Ji, Xinlei; Zhao, Jiahui; Li, Huanhuan; Pizzagalli, Diego A.; Law, Samuel; Lin, Pan; Fan, Lejia; Zhang, Panwen; Fang, Shulin; Wang, Xiaosheng; Yao, Shuqiao; Wang, Xiang
Abstract: Objective: We explored the neural mechanisms underlying disadvantageous risk decision making in un-medicated major depressive disorder patients who had recent suicide attempts. Methods: 53 patients with major depressive disorder (MDD), including 23 with a history of suicide attempts (SA) and 30 without (NS), and 30 healthy controls (HCs) completed pertinent psychometric assessments, and the dynamic decision making balloon analogue risk task (BART) under fMRI. We also built a 4-parameter Bayesian computational modeling for decision making analyses. Results: Several distinct findings emerged. First, SA patients had no depression intensity difference but higher pain avoidance in psychometrics, and more risk aversion in the BART when compared to the NS patients, with computational modeling confirming such reduced risk-taking propensity. Second, SA patients showed smaller left insular cortex activation than NS patients during the high risk, decisional phase of BART, and the modulation correlated with pain avoidance in both SA and NS groups. Third, during feedback phase of loss trials of the BART, SA patients had greater activation in the left dorsolateral prefrontal cortex (dlPFC) than NS patients. Conclusion: Taken together, we present novel findings and propose interpretations that the differential insula activation likely relates to high uncertainty-aversion in SA patients, contrary to the typical view that they are impulsive and risk prone. The differential left dlPFC activation likely suggests hypersensitivity to loss, contributing to conservative decision-making at large, and extreme choices such as suicide when value estimations are compromised and emotionally overwhelmed. The interactive interpretation places a renewed focus on psychological pain avoidance as a robust motivator for suicidal behavior. Highlights: Higher psychological pain avoidance and a reduced risk-taking propensity in BART in MDD with SA. Insula and dlPFC may play key role in decision-making in uncertainty context in MDD with SA. The strong drive to escape psychache may cause SA via biased decision-making of under-valuing life. Innovative computational modeling approaches were used.